2021
DOI: 10.3390/ani11030667
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence in Household Domestic Ferrets (Mustela putorius furo)

Abstract: Animal infections with SARS-CoV-2 have been reported in different countries and several animal species have been proven to be susceptible to infection with SARS-CoV-2 both naturally and by experimental infection. Moreover, infections under natural conditions in more than 20 mink farms have been reported where humans could have been the source of infection for minks. However, little information is available about the susceptibility of pet animals under natural conditions and currently there is no SARS-CoV-2 epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
2
43
0
3
Order By: Relevance
“…Multiple studies have now demonstrated that ferrets may be directly infected by human-derived SARS-CoV-2 and, following infection, exhibit a nearly 100% transmission rate via direct contact ( 9 , 10 , 18 , 19 , 29 ). Recent reports also describe sporadic cases of natural infection ( 30 , 31 ). However, our data suggest that the initial barrier of human-to-ferret transmission may be higher than relevant to most household pets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have now demonstrated that ferrets may be directly infected by human-derived SARS-CoV-2 and, following infection, exhibit a nearly 100% transmission rate via direct contact ( 9 , 10 , 18 , 19 , 29 ). Recent reports also describe sporadic cases of natural infection ( 30 , 31 ). However, our data suggest that the initial barrier of human-to-ferret transmission may be higher than relevant to most household pets.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence of SARS-CoV-2 transmission to ferrets, a finding at odds with the high transmission rates observed in laboratory and mink farm settings. Further evidence of natural transmission to household ferrets has exhibited a lower prevalence than those seen in dogs and cats, with only one currently confirmed case worldwide ( 15 , 30 , 31 ). To investigate whether viral or host genetics played a role in this discrepancy, we utilized available data for analysis and biologically relevant hypothesis generation using computational tools.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of SARS-CoV-2 throughout vast human populations worldwide has resulted in reports of transmission to animals living in close association with infected people [ 5 , 10 ]. Indeed, SARS-CoV-2 has been detected in pet and stray cats ( Felis silvestris catus ) [ 5 ], in tigers ( Panthera tigris ) and lions ( Panthera leo ) from zoos [ 11 ], in domestic ferrets ( Mustela putorius furo ) [ 12 , 13 ] and also in American mink ( Neovison vison ) on fur farms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high seroprevalence and SARS‐CoV‐2 detection rates in cats and to some extent in dogs indicate that these animals can be infected with SARS‐CoV‐2 ( Fritz et al, 2021 ; Hamer et al, 2020 ; Hosie et al, 2021 ; Leroy et al, 2020 ). Recent reports also describe sporadic cases of natural infection in household pet ferrets ( Mustela putorius furo ) in Slovenia and Spain ( Giner et al, 2021 ; OIE, 2021a ; ProMED-mail, 2020d ). These reports suggest that the impact of SARS‐CoV‐2 infections on domestic animal health is unclear.…”
Section: Sars-cov-2 Reverse Zoonosis and Secondary Zoonosismentioning
confidence: 99%